Assessing the sustainability of the co-operative programme in promoting local economic development In Sassa Gauteng province - Matlou, Matsobane Themba (University of the Witwatersrand, Johannesburg, 2024)
This qualitative single case study assesses the sustainability factors within the South African Social Security Agency's (SASSA) co-operative program, with a focus on how it promotes Local Economic Development (LED) in the Gauteng Province. Positioned as a catalyst for socioeconomic progress, this initiative seeks to empower local communities—particularly women, youth, and individuals with disabilities—through co- operative enterprises. Within this program, careful selections of co-operatives, were sampled for the study. The sampled co-operatives showcase the program's extensive reach and dedication to promoting inclusive local economic development in Gauteng province. Rooted in sustainability theory, the study explores co-operative sustainability, funding sufficiency, skills training and capacity building effectiveness, and program evaluation initiatives. The literature review integrates sustainability theory, emphasising program sustainability factors highlighted in scholarly literature. The methodology applied, included qualitative interviews and document analysis, in addition, the study engaged a number of key stakeholders for a comprehensive understanding of the phenomenon, enhancing reliability and validity. The research reveals critical insights into the co-operative program's sustainability. Key strategic measures, such as long-term contracts and stable funding, underscore the program's financial sustainability while emphasising the need for collaboration through stakeholder engagement. Challenges, including delayed payments, reliance on loans, and limited access to partnerships and grants, highlight the necessity for proactive measures like diverse funding models, improved financial practices, and enhanced resource access. Targeted skills training and capacity building illuminate the significance of education in sustaining co-operatives, and robust program evaluation showcases a commitment to continuous improvement. SASSA's co-operative initiative contributes considerably to Local Economic Development (LED) by creating jobs, increasing economic community empowerment, and improving educational outcomes (school uniforms). The study advocates for a review of financial support policies, reforms to Small, Medium, and Micro Enterprises (SMME) procurement policies to reduce competition with larger businesses, targeted ii skill development policies for co-operative members, and the establishment of a formalised evaluation framework to improve the program's effectiveness and sustainability. Aligned with South Africa's national and global commitment to the United Nations' 2030 Sustainable Development Goals, these proposals represent proactive steps toward advancing LED in Gauteng Province.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; co-operative programme; Sassa Gauteng province; SDG-8: Decent work and economic growth